Artificial Intelligence in Public Administration: Opportunities and Challenges in the Hungarian Context - Bihari, Éva Sarolta (Közigazgatási és Infokommunikációs Jogi PhD Tanulmányok, 2025)
This study explores the transformative role of artificial intelligence in public administration, with particular regard to Hungarian conditions. While AI offers efficiency, transparency, and improved citizen engagement, challenges arise from digital inequality, infrastructural disparities, and data protection concerns. The analysis stresses that AI should supplement rather than replace human judgment, requiring ethical, transparent, and citizen-centred implementation tailored to Hungary’s specific context.